Investing in People: The Labour Market Impact of Human Resource Interventions Funded under the 1994-1999 Community Support Framework in Ireland - Denny, K; Harmon, C; O'Connell, Philip J. (ESRI, 2000)
This paper produced a rigorous analysis of the human resource interventions which formed an important part of the EU Community Support Framework implemented in Ireland in the period 1994 to 1999. The study investigates the impact of both initial education and of continuing education, training and temporary employment programmes. The study utilises an approach based on comparison groups garnered from existing ESRI databases to estimate the net impact of the interventions rather than relying simply on cruder measures such as gross placement rates. Estimates are given of the returns to fourteen schemes included in the Support Framework in terms of income and employment prospects. The results suggest that programmes with strong market linkages are much more effective than those with a more general remit. On this basis, recommendations are made for a strategic re-orientation of labour market policies for the unemployed.